Logistic service quality as a mediator between logistics capabilities and customer satisfaction - Daniel Winter Fernandes; Roberto Giro Moori; Valdir Antonio Vitorino Filho (REGE Revista de Gestão, 2018)
Purpose - A way that companies have found to respond to the challenges of customer satisfaction (CS) is the development logistics services quality. In this sense, the purpose of this paper is to estimate the quality of logistical service as a mediator factor in the relationship between logistics capabilities (LC) and CS. For this, an exploratory survey of the descriptive type was carried out with 117 companies in the Brazilian market of lubricant oil. The collected data, modeled in structural equations, have shown evidence that the quality of logistics services totally mediates the relation between the LC and the satisfaction of clients. Design/methodology/approach - In order to respond to the research problem and to meet the stated objective, a study was carried out in two phases. The first used an exploratory qualitative design, and involved recorded in-depth interviews with five clients and five managers of a lubricant oil producer located in the municipality of Umuarama and nearby areas in Paraná state, Brazil. The second used an exploratory survey of the descriptive type was carried out with 117 companies in the Brazilian market of lubricant oil. Findings - The collected data, modeled in structural equations, have shown evidence that the quality of logistics services totally mediates the relation between the LC and the satisfaction of clients. Research limitations/implications - It is suggested that new studies be conducted in order to increase the size of the sample, since the number of responses obtained (117 respondents), for the number of initial variables (34 measures). Practical implications - In the pursuit of CS, the managers of lubricant oil producers should make major investments in LC, to enable the company to be active in the search for logistics solutions, integration and provision of reliable information to its customers. Social implications - The studies should also be carried out in other market segments, in order to compare the results obtained in the lubricating oil segment of Brazil and corroborate knowledge about the influence of logistical capabilities on the relation between logistics service quality and CS. Originality/value - The logistics services quality perceived by the customers is derived from the service capacity of the producer’s employees and the quality of information provided to the customers.